2022
DOI: 10.3389/fagro.2022.930378
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathy: an eco-friendly approach to control palmer amaranth using allelopathic sweetpotato

Abstract: Palmer amaranth (PA) is one of the major weeds in sweetpotato reducing its quantity and quality. The widespread and repeated use of chemical herbicides has led PA to develop resistance for such chemicals. In addition, chemical herbicides are incompatible with the organic production system. It is imperative to find sustainable weed management strategies to provide weed control suitable for organic cultivation and detain the development of herbicide-resistant weeds under conventional crop production. In the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…The decrease in chlorophyll levels can be linked to reduced mineral absorption and disruptions in the regulatory mechanisms responsible for chlorophyll synthesis (Siyar et al, 2019). The reduction of chlorophyll content in target plants due to the allelopathy effect was similar to those reported by Ma et al (2020), Li et al (2022) and Singh et al (2022). In addition, the experiment revealed that the length of stomata in the choisum compared to the control decreased by up to 34.21% when subjected to 100 mg mL -1 (Figures 2A-2B).…”
Section: Effect Of Vetiver Root Methanolic Extract On Chlorophyll Con...supporting
confidence: 77%
“…The decrease in chlorophyll levels can be linked to reduced mineral absorption and disruptions in the regulatory mechanisms responsible for chlorophyll synthesis (Siyar et al, 2019). The reduction of chlorophyll content in target plants due to the allelopathy effect was similar to those reported by Ma et al (2020), Li et al (2022) and Singh et al (2022). In addition, the experiment revealed that the length of stomata in the choisum compared to the control decreased by up to 34.21% when subjected to 100 mg mL -1 (Figures 2A-2B).…”
Section: Effect Of Vetiver Root Methanolic Extract On Chlorophyll Con...supporting
confidence: 77%
“…PCA and clustering have been used to group allelopathic weed-suppressive cotton lines based on their weed-suppressive potential, which can aid in gaining a deeper insight into breeding material for crop enhancement (Fuller et al, 2021) [2]. Similarly, the grouping of rice cultivars by Schumaker et al (2020) [19] and sweet potato varieties by Singh et al (2022) [25] has been carried out using similar strategies. Allelopathy often occurs as a response to challenging conditions, as noted by Kruse and a group of researchers in their study published in 2000.…”
Section: Discussionmentioning
confidence: 99%
“…Using the stairstep structure created an avenue for determining the possible allelopathic effect of the donor plant (cotton lines) on the recipient plant (PA seedlings). In previous studies, the stairstep structure has been used to assess the allelopathic potential of Oryza sativa in relation to Echinochloa crus-galli [ 19 ] and Gossypium hirsutum against A. palmeri [ 2 ] and Ipomoea batatas against A. palmeri [ 25 ].…”
Section: Discussionmentioning
confidence: 99%